PENGARUH INFLUENCER SOCIAL MEDIA DAN CONTENT MARKETING TERHADAP MINAT BELI GENERASI Z DI KOTA PALOPO - Rudi, Rudi; Ikbal, Muhammad; Hapid, Hapid (Politeknik Negeri Ambon, 2025)
Introduction: The advancement of digital technology has transformed the marketing landscape, particularly in reaching Generation Z, who have grown up within the social media ecosystem. Influencer and content marketing have become increasingly popular strategies, as they are believed to shape opinions and drive purchase intention among young consumers.Methods: This study aims to analyze the influence of social media influencers and content marketing on Generation Z's purchase intention in Palopo City. A quantitative approach was employed, using a survey method that involved 133 respondents selected through purposive sampling. Data analysis was conducted using multiple linear regression with the assistance of SPSS 25.Results: The results show that both independent variables have a positive and significant effect on purchase intention, both partially and simultaneously. The coefficient of determination (R²) value of 0.541 indicates that 54.1% of the variation in purchase intention can be attributed to the influence of social media influencers and content marketing. These findings reinforce the role of digital marketing in supporting MSME growth strategies through the targeted use of social media.Keywords: Influencer, Content Marketing, Purchase Intention, Generation Z, Digital Marketing